Comments on "Kinematic variations across Eastern Cordillera at 24°S (Central Andes): Tectonic and magmatic implications" by Acocella, et al. [Tectonophysics 434 (2007) 81-92] - Petrinovic, Ivan Alejandro (2009)
The interpretation of Acocella et al. about (i) westward increase of strike-slip motion, (ii) strain partitioning, (iii) symmetry of the Central Andes, as well as (iv) the interpreted cause for the occurrence of magmatic centres behind the arc, from the Late Miocene onward, is largely speculative and contains major flaws. We demonstrate all above, that successive phases of deformation from Middle Eocene to Quaternary in the edge of the Puna-Eastern Cordillera, as well as the occurrence of arc/intraplate signatures in the magmatic centres of the Eastern Cordillera, result in complex geological framework which requires more detailed and intensive work in order to achieve sustainable interpretations.